ECONOMIC EFFICIENCY IN THE PRODUCTION OF CREAM-PERFUMED SOAP - Yulchiev, Aslbek; Shukhratbek, Sherzodbek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article presents the results of a study aimed at determining the expected economic efficiency in the production of cream-perfumed soaps based on non-traditional oil-based raw materials. The research includes data on the quantity and cost of raw materials used for producing cream-perfumed soap, as well as the total annual profit.